Queensland: kookaburra maths outcomes 1 - Dean, Dean , Vanessa; Nightingale, Paul (Thomson Learning Australia Southbank, 2004)
he book emphasizes hands-on learning, promoting critical thinking and numeracy skills in young children. It covers key areas such as counting, number recognition, basic operations, and geometry, aligning with educational standards to ensure a comprehensive understanding of mathematics. With its vibrant illustrations and interactive approach, this resource aims to foster a positive attitude towards math, setting the stage for future learning.